The role of fur in the acid tolerance response of Salmonella typhimurium is physiologically and genetically separable from its role in iron acquisition. - Hall, H K (1996)
The response of Salmonella typhimurium to low pH includes a low-pH protection system called the acid tolerance response (ATR). The iron-regulatory protein Fur has been implicated in the ATR since fur mutants are acid sensitive and cause altered expression of several acid shock proteins (J. W. Foster, J. Bacteriol. 173:6896-6902, 1991). We have determined that the acid-sensitive phenotype of fur mutations is indeed due to a defect in Fur that can be complemented by a fur(+)-containing plasmid. However, changes in cellular iron status alone did not trigger the ATR. Cells clearly required exposure to low pH in order to induce acid tolerance. The role of Fur in acid tolerance was found to extend beyond regulating iron acquisition. A mutation in fur converting histidine 90 to an arginine (H90R) eliminated Fur-mediated iron regulation of enterochelin production and deregulated an iroA-lacZ fusion but had no effect on acid tolerance. The H90R iron-blind Fur protein also mediated acid shock induction of several Fur-dependent acid shock proteins and acid control of the hyd locus. In addition, a Fur superrepressor that constitutively repressed iron-regulated genes mediated normal Fur-dependent acid tolerance and pH-controlled gene expression. The results indicate the acid-sensing and iron-sensing mechanisms of Fur are separable by mutation and reinforce the concept of Fur as a major global regulator in the cell.